Analisis Sistem Pendukung Keputusan Penerima Beasiswa Terbaik Menerapkan Metode Weight Aggregated Sum Product Assesment (WASPAS) dengan Pembobotan Rank Order Centroid (ROC) - Sopyan, Yayan; Lesmana, Agria Dwi (Building of Informatics, Technology and Science (BITS), 2022)
KIP Kuliah is one of the government's education equity programs. The KIP Kuliah program is intended for students who graduate from high school or its equivalent, but not all students can benefit from the KIP Kuliah program. Students who are entitled to benefit from the KIP Kuliah program are those who have academic potential but whose economic circumstances do not allow them to continue their education at tertiary institutions. The process of selecting scholarship recipients is a new problem for tertiary institutions, where quotas and the number of applicants are sometimes unbalanced, so a rigorous selection process is needed based on an assessment of the economic condition of the family and the achievements of the scholarship recipient candidates. Therefore, a Decision Support System (DSS) is needed to overcome this problem using the Weighted Aggregated Sum Product Assessment (WASPASS) and rank order centroid (ROC) methods to find the best alternative scholarship recipients. The results obtained from this study are the recipients of the best alternative scholarship A6, with the highest score of 0.57, followed by other alternatives based on the ranking results in this DSS calculation.